Unusual magnetic resonance findings in two children with sudden sensorineural hearing loss Achados incomuns nas ressonâncias magnéticas de duas crianças com perda auditiva neuro-sensorial súbita - Emerson L. Gasparetto; Arnolfo de Carvalho Neto; Danny Warszawiak; Isac Bruck; Sérgio Antoniuk; Lúcia H.C. dos Santos (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To describe the MRI findings of two pediatric patients with sudden sensorineural hearing loss (SSHL). CASE REPORTS: Two male patients (two-year and three-months-old, and one year and four-months-old) presented with sudden dumbness. Physical and neurological examinations were unremarkable besides bilateral hypoacusia. All the laboratory investigation was negative, and brain stem auditory evoked potentials showed deep bilateral deafness in both cases. MRI studies revealed normal inner ears and multifocal white matter areas of slight low signal on T1-weighted images and high signal on FLAIR images. The follow-up MRI studies and neurological examinations did not demonstrate alterations in the previous findings. CONCLUSION: Pediatric patients with SSHL may present cerebral white matter signal abnormalities at the MRI as the only finding. Further studies with larger casuistics need to be conducted to elucidate these findings. OBJETIVO: Descrever os achados de ressonância magnética (RM) em dois pacientes pediátricos com perda auditiva neuro-sensorial súbita (PANS). RELATO DOS CASOS: Dois pacientes masculinos (dois anos e três meses e um ano e quarto meses de idade) apresentaram-se com surdez súbita. Os exames físico e neurológico foram normais, à exceção da hipoacusia. Toda a investigação laboratorial foi normal, e os potenciais auditivos evocados do tronco cerebral demonstraram surdez profunda bilateral. Os exames de RM evidenciaram estruturas normais dos ouvidos internos e áreas multifocais de discreto hipossinal em T1 e hipersinal em FLAIR na substância branca dos hemisférios cerebrais. As RMs e os exames neurológicos de controle não demonstraram alterações nos achados prévios. CONCLUSÃO: Pacientes pediátricos com PANS podem apresentar à RM alterações de sinal na substância branca dos hemisférios cerebrais como único achado. Estudos futuros com casuísticas maiores deverão ser conduzidos para a elucidação destes achados.